62.9k views
4 votes
Consider the function F(x) = - 2x + 3x - 8. Determine F(k + 4).

User Coree
by
4.9k points

1 Answer

4 votes

Answer:

F(k + 4) = k - 4

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property

Algebra I

  • Function Notation
  • Combining Like Terms

Explanation:

Step 1: Define

F(x) = -2x + 3x - 8

F(k + 4) is x = k + 4

Step 2: Find F(k + 4)

  1. Substitute in x: F(k + 4) = -2(k + 4) + 3(k + 4) - 8
  2. Distribute -2: F(k + 4) = -2k - 8 + 3k + 12 - 8
  3. Combine like terms (k): F(k + 4) = k - 8 + 12 - 8
  4. Combine like terms (Z): F(k + 4) = k - 4
User Starasia
by
4.3k points